Research in finance. Vol. 26 - Kensinger, John W. (Emerald, 2010)
For the last twenty years the Research in Finance book series has been publishing papers that cover issues of significance and interest in finance and economics. The topics found in the series span a wide range and have made substantial contributions to the literature with articles from key figures in the world of finance. Volume 26, Coping with Systemic Risk, is no exception and provides a valuable addition to the current research of finance in this area. The lead chapter sets the theme by giving insight into economic systems as packages containing multiple real options where the rational exercise of these options then shapes the outcomes from the system. Remaining chapters explore the use of commodities like oil as a means of improving the diversification of portfolios containing equities, reliability tests for traditional accounting measures to predict the onset of financial distress, the behavior of metal prices such as aluminium and steel, and other issues relevant for a better-diversified investor. Key reading for academics and practitioners alike, its audience will range from financial economists and accountants in academia to executives with financial duties.